2012
DOI: 10.1111/j.1365-4632.2011.05080.x
|View full text |Cite
|
Sign up to set email alerts
|

Cojedes: a leprosy hyperendemic state

Abstract: This study confirms that several communities in Cojedes State have extremely high leprosy rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
3
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 12 publications
(12 reference statements)
2
3
0
1
Order By: Relevance
“…Hyperendemic areas were kept under permanent surveillance and 63 new cases were detected in 2009 through active house-to-house searches for case activities. Similar trends were also observed in other communities (Aranzazu et al 2012). In this study, we identified new leprosy cases within hyper-endemic areas in the central plains of Venezuela using ELISA with recombinant mycobacterial proteins ML0405, ML2331 and LID-1.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Hyperendemic areas were kept under permanent surveillance and 63 new cases were detected in 2009 through active house-to-house searches for case activities. Similar trends were also observed in other communities (Aranzazu et al 2012). In this study, we identified new leprosy cases within hyper-endemic areas in the central plains of Venezuela using ELISA with recombinant mycobacterial proteins ML0405, ML2331 and LID-1.…”
Section: Discussionsupporting
confidence: 81%
“…This test can easily be performed by the community nurse, which permits an early diagnosis for patients with corresponding benefits. Analysis of the antigen-specific antibody responses of leprosy patients in Mamaría confirmed a differential antibody response between MB and PB patients and similar results have been found in other Venezuelan communities (Duthie et al 2011, Aranzazu et al 2012. The antibody response was elevated in MB patients, which correlated with increased bacterial loads.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…1 Similarly, in China, new sporadic indigenous cases are successively reported throughout most of the provinces, especially in the economically underdeveloped regions. In 1997, Venezuela reached the goal of elimination of leprosy as a public health problem.…”
Section: Discussionmentioning
confidence: 98%
“…Heute, über 140 Jahre nach Entdeckung des Bakteriums und 40 Jahre nach der durch das Deutsche Aussätzigen-Hilfswerk geförderten Einführung der ersten "Multidrug-Therapy" (MDT) durch Freerksen [5,6], ähnelt die Verteilung neuer Fälle in aktuellen Endemiegebieten der Situation in Europa zur Zeit Hansens: Zwischen Regionen mit zurückgehenden Inzidenzdaten persistieren Enklaven mit hoher Durchseuchung und Prävalenz [7,8]. Andererseits läuft weltweit die Entwicklung, die einst in Mitteleuropa der Lepra ihren Schrecken genommen hat, weiter [9,10].…”
unclassified